The Quality of College Life from Viewpoint of Native and Non-Native Students of Tehran’s Public Universities - Reza Mahdi (Taḥqīqāt-i Farhangī-i Īrān, 2016)
The quality of college life means the overall satisfaction of students from the college life as a whole which is affected by different aspects of life based on the theory of generalization. The aim of this study is to evaluate the quality of college life among local and non-local students from non-state universities in Tehran. This study is developmental with respect to the aim and uses survey method for data gathering. The statistical population of the study are undergraduate students and 500 samples are chosen from the universities in the target population randomly and data are gathered using the questionnaire designed by the researcher the validity of the questionnaire has been verified based on the views of 5 experts and using some similar tested questionnaires as a model. The reliability has been estimated using Alpha Cronbach’s index by pre-test of 15 samples about 0.86. To data analyze SPSS software and statistical tests are used. The quality of the college life of students has been evaluated significantly lower than average and the quality of college life of non-local students is significantly higher than the quality of college life of local students. The low quality of college life shows that higher education policies on quality and national resources productivity have had low effectiveness. Dissatisfaction of students, as the key stakeholder of higher education system, from quality of college life could be a starting point to stray away from the higher education missions and philosophies. It is necessary that academic managers and leaders make serious decisions to promote the quality of college life. The higher education without the quality of college life, will be defeating the purpose.